Compression of video and audio signals and expansion of a compressed signal in accordance with an image hf component compression factor - UEDA; HIROAKI (1997)
On expanding, into a video reproduction and an audio reproduction synchronized with each other, a compressed video and audio signal comprising subsampled video and audio codes and indicating a frame rate and an indicated high frequency compression factor, presubsampled video codes are reproduced in compliance with the frame rate and decoded into decoded images. In compliance with a high frequency component compression factor selected from table factors in accordance with the indicated high frequency component compression factor, a dequantizer dequantizes the decoded images into dequantized images. In compliance with another high frequency component compression factor likewise selected, an inverse discrete cosine transform processing unit subjects the dequantized images to inverse discrete cosine transform to produce the video reproduction.